The behaviour change technique: Profile of a multimodal lifestyle intervention - Anja Englund; Johan Nilsson Sommar; Benno Krachler (Lifestyle Medicine, 2024)
Abstract Introduction The behaviour change technique taxonomy version 1 was developed to identify the smallest active ingredients of a lifestyle intervention, that is, behaviour change techniques (BCTs) based on a written description. By participation and direct observation of an intervention, we intend to not only identify BCTs but also assess exposure time for each BCT. Adding the dimension of exposure time should enable us to make quantitative comparisons between the different BCTs employed. We intend to demonstrate this by studying the hypotheses that exposure to information‐related BCTs is similar for all targeted lifestyle modalities but decreases in the course of the intervention. Methods During 5‐week intensive multimodal lifestyle interventions at a Swedish clinic for lifestyle medicine, we identified BCTs according to behaviour change technique taxonomy version 1 and noted exposure times to BCTs in all mandatory parts of the behaviour change intervention. Results Two hundred thirty‐one independent intervention components were evaluated. BCTs 8.1 Behavioural practice/rehearsal (126 h), 4.1 Instruction on how to perform the behaviour (98 h) and 6.1 Demonstration of the behaviour (65 h) were the most common in terms of exposure time. Relative exposure to BCTs with an informative nature was similar for the different treatment phases (33%−37%−28%; p = 0.09) but higher for physical activity compared to food habits, stress management and unspecific lifestyle medicine (63%−25%−22%−25%; p < 0.001). Conclusions The behaviour change technique taxonomy version 1 can be extended by adding exposure time for different BCTs. The resulting BCT–exposure profile can be used for assessing the relative importance of different behaviour change strategies.